2003
DOI: 10.1172/jci200319429
|View full text |Cite
|
Sign up to set email alerts
|

Sex is a potent modifier of the cardiovascular system

Abstract: Despite the growing number of reports in the literature identifying sex-related differences in cardiac function in both rodents and humans, the underlying mechanisms have yet to be determined. Here, variables of experimental studies such as diet, animal model utilized, and age, in addition to sex hormones and other factors that may play a role in sex-related variations in cardiac responses to various pathophysiological conditions are discussed, suggesting that current approaches used in the study of cardiac di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(43 citation statements)
references
References 61 publications
(25 reference statements)
1
40
0
Order By: Relevance
“…The exact molecular mechanism is still unknown, but the hypothesis is that estrogen prevents the development of cardiovascular diseases that could culminate into CHF [37]. However, this was challenged by the findings that estrogen replacement in postmenopausal women actually increased heart disease [46]. Thus, our Cap2 gene-trap model may serve as a good addition to current DCM models to understand the molecular basis of DCM and sex differences in DCM progression.…”
Section: Discussionmentioning
confidence: 99%
“…The exact molecular mechanism is still unknown, but the hypothesis is that estrogen prevents the development of cardiovascular diseases that could culminate into CHF [37]. However, this was challenged by the findings that estrogen replacement in postmenopausal women actually increased heart disease [46]. Thus, our Cap2 gene-trap model may serve as a good addition to current DCM models to understand the molecular basis of DCM and sex differences in DCM progression.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced insulin sensitivity or upregulated expression of androgen receptor within the heart has been found to impair cardiac function. 104 , 105 The upregulation of androgen receptor that we observed within the PNA heart may alter the electrophysiology of the cardiomyocytes of the left ventricle by altering expression of receptors involved in the regulation of membrane potential. 106 , 107 Androgens may promote the development of cardiomyopathy by upregulating potassium channel regulatory subunits and reducing cardiomyocyte repolarization.…”
Section: Discussionmentioning
confidence: 94%
“…In most cardiovascular diseases, premenopausal women have a much better prognosis than men [1]. It has also been demonstrated that females fare better than their male counterparts after cardiac ischemia-perfusion injury [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that females fare better than their male counterparts after cardiac ischemia-perfusion injury [2,3]. On the other hand, women with idiopathic dilated cardiomyopathy have a poorer prognosis than males, and women are also more susceptible to alcohol-related heart disease [1]. Pulmonary arterial hypertension occurs twice as frequently in females as compared to males [4][5][6].…”
Section: Introductionmentioning
confidence: 99%